2019
DOI: 10.1080/23802359.2019.1643797
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitogenome of the splendid japalure Japalura splendida (Squamata, Agamidae)

Abstract: The complete mitogenome of Japalura splendida (16,673 bp in length) is determined and analyzed in this study. It contains 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes, and one non-coding regions. All the genes in J. splendida are distributed on the H-strand, except for the ND6 gene and seven tRNA genes which are encoded on the L-strand. The phylogenetic tree suggests that J. splendida and Japalura flaviceps formed a sister group and reveals the order ((((Acanthosaura lepidogaster, Acanthosaura armata),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Seven PCGs terminated with complete stop codons, TAA ( ND4L , ND5 ), AGG( ND1 ), AGA ( COX1 ), CAC ( ATP8 ), and TAG ( ND2 , and ND6 ), while the other six genes ended with the incomplete stop codon, TA/T ( COX2 , ATP6 , COX3 , ND3 , ND4 , and Cytb ). The mitogenome content and structure of D. vela was consistent with the previously published representatives of the family (Liu et al 2019 ; Huang et al 2019 ; Li et al 2021 ).…”
supporting
confidence: 90%
“…Seven PCGs terminated with complete stop codons, TAA ( ND4L , ND5 ), AGG( ND1 ), AGA ( COX1 ), CAC ( ATP8 ), and TAG ( ND2 , and ND6 ), while the other six genes ended with the incomplete stop codon, TA/T ( COX2 , ATP6 , COX3 , ND3 , ND4 , and Cytb ). The mitogenome content and structure of D. vela was consistent with the previously published representatives of the family (Liu et al 2019 ; Huang et al 2019 ; Li et al 2021 ).…”
supporting
confidence: 90%
“…Here, we also found that the C. mystaceus mitogenome had a trnP gene encoded by the heavy strand, similar gene arrangement has been found in other south and southeast Asia species of Draconinae (Amer and Kumazawa 2007 ; Huang et al. 2019 ). Eleven PCG S were initiated with ATG, except two PCG S ( nad2 and nad4l ) starts with ATT.…”
supporting
confidence: 85%
“…However, few investigations have been conducted on the microbial communities of reptiles [5]. The Chinese tree dragon (Japalura sensu lato) is primarily distributed in the Yangtze River Basin in southwestern China, including the Yunnan, Sichuan, Chongqing, and Hubei provinces [6]. These lizards often appear on the edge of forests among shrubs and gravel.…”
Section: Introductionmentioning
confidence: 99%